Life Outside your Comfort Zone: The Power of Reflection for Cultural Adjustment - Sy, Jobila; Cruz, Natalie (Journal of International Students, 2019)
This reflective paper explores the different experiences of two higher education professionals who utilized intentional reflection to help with the transition to new countries and cultural environments. One story focuses on how the higher education professional grappled with different challenges even though her new environments afforded her a novel privilege of membership in a racial and religious majority. The other higher education professional’s story discusses her transition from life as a member of the majority to a member of the minority in a different religious and racial context. The paper concludes by sharing recommendations for how other higher education professionals can utilize reflection (Dewey, 1993; Rodgers, 2002) to help with a transition and cultural adjustment in a new environment.